2013
DOI: 10.1155/2013/768108
|View full text |Cite
|
Sign up to set email alerts
|

Social Learning in Bumblebees (Bombus impatiens): Worker Bumblebees Learn to Manipulate and Forage at Artificial Flowers by Observation and Communication within the Colony

Abstract: Social learning occurs when one individual learns from another, mainly conspecific, often by observation, imitation, or communication. Using artificial flowers, we studied social learning by allowing test bumblebees to (a) see dead bumblebees arranged in foraging positions or (b) watch live bumblebees actually foraging or (c) communicate with nestmates within their colony without having seen foraging. Artificial flowers made from 1.5 mL microcentrifuge tubes with closed caps were inserted through the centres o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…To this end, our bees used a combination of simple forms of learning. Consistent with a previous study [ 55 ], during observation, bees were able to pick up the location of a new access to the reward (local enhancement of flower position). In addition, we showed that the observers were attracted to the string (stimulus enhancement).…”
Section: Discussionsupporting
confidence: 88%
“…To this end, our bees used a combination of simple forms of learning. Consistent with a previous study [ 55 ], during observation, bees were able to pick up the location of a new access to the reward (local enhancement of flower position). In addition, we showed that the observers were attracted to the string (stimulus enhancement).…”
Section: Discussionsupporting
confidence: 88%
“…It has long been known that during foraging, bees are attracted to visibly occupied flowers [e.g., bumblebees (Brian, 1957); stingless bees (Slaa et al, 2003); honey bees (Von Frisch, 1967), suggesting that they learn to exploit food resources by copying the choices of other bees (Romanes, 1884)]. Recent studies with bumblebees have shown that individuals can indeed glean information from watching other foragers, and change accordingly their floral choices (Leadbeater andChittka, 2005, 2007a;Worden and Papaj, 2005;Kawaguchi et al, 2007;Baude et al, 2011;Avarguès-Weber and Chittka, 2014a,b), their choice of location (Leadbeater andChittka, 2005, 2009;Kawaguchi et al, 2006;Baude et al, 2008;Dawson and Chittka, 2012;Plowright et al, 2013) and their handling strategies (Leadbeater and Chittka, 2008;Goulson et al, 2013;Mirwan and Kevan, 2013).…”
Section: Observational Learning In Bees Behavioral Evidencesmentioning
confidence: 99%
“…Here we sought to uncover the mechanisms implemented by flying insects in gap identification and perception. Bumblebees are excellent model organisms because much is known about their flight and navigational performance (Baird and Dacke, 2012; Crall et al, 2014; Mirwan and Kevan, 2013; Osborne et al, 2008; Ravi et al, 2013; Riabinina et al, 2014; Lobecke et al 2018). We presented unsuspecting bumblebees with an altered environment consisting of a wall obstructing their flight path but containing a gap that prevented direct passage to their goal and observed their behavior as they approached and traversed the gap.…”
Section: Introductionmentioning
confidence: 99%